2014
DOI: 10.1016/j.socscimed.2013.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Parenting with bipolar disorder: Coping with risk of mood disorders to children

Abstract: Children of individuals with bipolar disorder (BPD) have increased risk for mood disorders and other adverse psychosocial outcomes due to genetic and environmental risk. Though parents with BPD are aware of increased risk to children, little is known about efforts undertaken in response or their perceived utility. Among parents who self-report with BPD, this study identifies key variables associated with parental coping with children’s risk of mood disorders; and explores the relationship between monitoring ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The relationship between representation of illness severity and adaptation was mediated by coping (Peay et al, 2013). Finally, severity perceived was not linked with parents' ability to cope with the risk of mood disorders in children (Peay et al, 2014).…”
Section: Illness Representations and Psychosocial Adjustment Of Peoplmentioning
confidence: 80%
See 1 more Smart Citation
“…The relationship between representation of illness severity and adaptation was mediated by coping (Peay et al, 2013). Finally, severity perceived was not linked with parents' ability to cope with the risk of mood disorders in children (Peay et al, 2014).…”
Section: Illness Representations and Psychosocial Adjustment Of Peoplmentioning
confidence: 80%
“…Four studies have explored the relationship between psychosocial adjustment and illness representations in people with a bipolar disorder (Lobban et al, 2013;Peay et al, 2013Peay et al, , 2014Dodd et al, 2017). Good recovery was associated with high levels of treatment and personal control and low levels of perceived consequences, emotional representations, identity, and self-blame (Dodd et al, 2017).…”
Section: Illness Representations and Psychosocial Adjustment Of Peoplmentioning
confidence: 99%
“…Neither study looked at how individuals with bipolar disorder balanced and negotiated these factors in making decisions about whether or not to have children. A 2014 study on parenting with bipolar disorder (Peay, Rosenstein, & Biesecker, 2014) found that individuals with bipolar disorder who used "active coping" with their own bipolar disorder, meaning that they proactively adjusted their lifestyle to prevent triggers for mood episodes, were more likely to use the same kinds of strategies for parenting their children. Our results also indicate that individuals' own experiences living with bipolar disorder influence their reproductive decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…More recent research has explored children's psychological risk (Peay, Rosenstein, & Biesecker, ), psychosocial functioning, and socio‐emotional development. Studies have indicated that children of parents with BD may not function as well those of ‘healthy’ parents in areas including life satisfaction, recreation, work, school, and interpersonal relationships (Bella et al ., ).…”
Section: Introductionmentioning
confidence: 99%